Long-Run Determinants of Exchange Rate Regimes : A Simple Sensitivity Analysis - Mauro, Paolo (IMF Working Papers; Working Paper, 2002)
Many studies have attempted to uncover empirical regularities in how countries choose their exchange rate regimes. We survey previous studies showing that, taken as a whole, the literature is inconclusive. Drawing on a large dataset with many potential explanatory variables and a variety of exchange rate regime classifications, we test old and new theories and confirm that no robust empirical regularities emerge.